Llanw - Ros, Manon Steffan (Y Lolfa, 2014)
Llanw, a young girl lives with Gorwel, her twin, and their grandmother in a cottage in a small coastal village in mid-Wales. The Second World War throws its shadow on the family, as Gorwel's decision has a detrimental effect on Llanw's life. Another exceptional novel by the author of Blasu. Intro – Y Lloer a'i Chariad – Mam Ni Oll – Nant y Dechrau – Noa – Chwibanu – Y Llanw a'r Gorwel – Pen Adele – Rhai Fel Ni – Gwydr Glas, Gwydr Du – Anadl – Y Nawfed Don – Gwylanod – Dros y Dŵr i Ynys-las – Cig – Y Sarah – Niwl – Tân – Breuddwyd – Celwydd – Sepia – Y Chwedl Olaf.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books